Advances in Regenerative Sports Medicine Research - Wang, Liren; Jiang, Jia; Lin, Hai; Zhu, Tonghe; Cai, Jiangyu; Su, Wei; Chen, Jiebo; Xu, Junjie; Li, Yamin; Wang, Jing; Zhang, Kai; Zhao, Jinzhong (Frontiers in Bioengineering and Biotechnology, 2022)
Regenerative sports medicine aims to address sports and aging-related conditions in the locomotor system using techniques that induce tissue regeneration. It also involves the treatment of meniscus and ligament injuries in the knee, Achilles’ tendon ruptures, rotator cuff tears, and cartilage and bone defects in various joints, as well as the regeneration of tendon–bone and cartilage–bone interfaces. There has been considerable progress in this field in recent years, resulting in promising steps toward the development of improved treatments as well as the identification of conundrums that require further targeted research. In this review the regeneration techniques currently considered optimal for each area of regenerative sports medicine have been reviewed and the time required for feasible clinical translation has been assessed. This review also provides insights into the direction of future efforts to minimize the gap between basic research and clinical applications.